A Competitiveness Strategy for America. Reports of the Subcouncils. Second Report to the President & Congress - Competitiveness Policy Council, Washington, DC.; Competitiveness Policy Council, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This publication contains detailed reports from the eight subcouncils established by the Competitiveness Policy Council to develop specific policy recommendations in eight areas. "Building a Standards-Based School System" (Education Subcouncil) recommends redirecting the education system toward achieving the National Education Goals, developing standards and new assessments, developing capacity of schools and youngsters to achieve high standards, and developing an incentive and accountability system. "Building High-Performance Workplaces" (Training Subcouncil) proposes a four-part economic strategy: build a training system that works, promote continual skills development, enhance school and work integration, and ease the adjustment process. "Technology Policy for a Competitive America" (Critical Technologies Subcouncil) recommends increasing national investment in civilian and dual-use research and development, promoting commercialization of strategic technology, creating a world-class technology base, and organizing organizations for results. "The Will to Act" (Subcouncil on Corporate Governance and Financial Markets) proposes improvements in the corporate governance process by corporation, shareholder monitoring in this process, and improved corporate performance evaluation. "A Trade Policy for a More Competitive America" (Trade Policy Subcouncil) recommends creation of an "export mentality," world growth strategies and exchange rate coordination, trade negotiations to open markets, export promotion, export disincentive reduction, and a streamlined trade bureaucracy. "Forging the Future: Policy for American Manufacturing" (Manufacturing Subcouncil) recommends leadership for manufacturing excellence, investment in manufacturing assets, and effective use of manufacturing assets. "Investing in Our Future" (Public Infrastructure Subcouncil) focuses on needs for action in the areas of efficient transportation, adequate financing, and advancement of new telecommunications technologies. "Saving, Investment, and the Budget" (Capital Formation Subcommittee) recommends two ways to increase national savings: raising private savings and reducing public spending. (YLB)
Availability: U.S. Government Printing Office, Superintendent of Documents, Mail Stop: SSOP, Washington, DC 20402-9328 ($19).
ERIC Note: For the related second annual report, see CE 063 486. For the first annual report, see ED 349 443.
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Capital; Competition; Dislocated Workers; Economic Development; Education Work Relationship; Educational Change; Elementary Secondary Education; Federal Government; Government Role; International Trade; Investment; Job Training; Labor Force Development; Manufacturing; Productivity; Retraining; Vocational Education; National Education Goals 1990; Reports, General